2019
DOI: 10.1111/fare.12352
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Father Involvement: An Intervention With Community and Child Welfare–Referred Couples

Abstract: Objective To expand the evidence base of the Supporting Father Involvement (SFI) intervention to include child welfare families. Background Taking a preventive father‐inclusive approach, SFI aims to strengthen coparenting, parent–child relationships, and child outcomes. This study replicates 4 prior iterations of the program using the same 32‐hour curriculum facilitated by clinically trained staff, case managers, and onsite child care and family meals. Method Participants (N = 239) included low‐income (median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 36 publications
6
48
0
Order By: Relevance
“…The intervention data in the current report are drawn from a Randomized Clinical Trial � (RCT) of the Supporting Father Involvement couples group intervention (Kline Pruett et al, 2019). We found that low-income parents' participation in the interventiona couples group meeting with clinically trained facilitators for 16 weeks -produced a significant reduction in couple conflict at two months post-intervention -a reduction still evident one year later.…”
Section: The Current Studymentioning
confidence: 91%
See 3 more Smart Citations
“…The intervention data in the current report are drawn from a Randomized Clinical Trial � (RCT) of the Supporting Father Involvement couples group intervention (Kline Pruett et al, 2019). We found that low-income parents' participation in the interventiona couples group meeting with clinically trained facilitators for 16 weeks -produced a significant reduction in couple conflict at two months post-intervention -a reduction still evident one year later.…”
Section: The Current Studymentioning
confidence: 91%
“…Details of the recruitment, retention, and intervention procedures can be viewed in Kline Pruett et al (2019). As described in earlier U.S. trials of SFI (Cowan, Cowan, Pruett, Pruett, & Gillette, 2014;Cowan, Cowan, Pruett, Pruett, & Wong, 2009), staff members for the present study were located within existing Family Resource Centers in five California counties -one urban, the other four primarily agricultural, all low-income communities.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants in the fathers-only groups showed increased involvement in the care of their children but declining relationship satisfaction, whereas mothers and fathers who attended the groups as couples reported increases in father involvement, declines in parenting stress, and stable levels of both relationship satisfaction and child behaviors over 18 months. We went on to replicate these findings with a second, more ethnically diverse sample (P. A. , and a third trial in which half of the families were referred by child welfare staff because of earlier domestic violence, child abuse, or neglect (Pruett, Cowan, Cowan, Gillette, & Pruett, 2019). In this latter, higher-risk sample, participation in a couples group intervention also produced statistically significant positive effects on reducing parents' relationship distress (conflict and violent problem-solving 2 months after the groups ended).…”
Section: Schoolchildren and Theirmentioning
confidence: 98%